Measurement of flow‐mediated dilation of mouse femoral artery in vivo by optical coherence tomography. Issue 11 (28th June 2018) - Song, Weiye; Zhou, Libo; Kot, Kevin L.; Fan, Huijie; Han, Jingyan; Yi, Ji
Abstract : Flow‐mediated vasodilation (FMD) is used for assessment of vascular endothelial function in humans as a predictor of cardiovascular events. It has been challenging to carry it on preclinical murine models due to the diminutive size of the femoral artery. Here, we present a new approach to accurately measure the blood velocity and femoral artery diameters of mice by acquiring Doppler optical coherence tomography and optical coherence tomography angiography continuously within 1 single experimental scanning protocol. Using the 3‐dimensional imaging and new velocity algorithm, the measurement precision of diameter, blood flow, velocity and wall shear stress are improved to 0.91%, 11.0%, 10.7% and 14.0%, respectively. FMD of healthy mouse femoral artery measured by this method was 11.96% ± 0.98%, which was blunted to 5.69% ± 0.4% by intravenous administration of endothelial nitric oxide synthase inhibitor (L‐N G ‐Nitroarginine methyl ester), in agreement with that reported in the literature. Abstract : Noninvasive estimation of flow‐mediated dilation (FMD) in living mice is challenging mainly due to the diminutive size of mouse femoral artery since FMD was established in 1992. Here, we develop a new optical coherence tomography (OCT)‐base image platform to measure FMD, wall shear stress, velocity and blood flow in living mice by combining OCT angiography and Doppler OCT in 1 scanning protocol. OCT is thus a powerful technique to the assessment of mouse vascular function.